Medication errors - B. K. Romanov; I. A. Toropova; E. Y. Kolesnikova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
The article presents the descri ption of the causes, detection methodsand approaches to the prevention of medication errors